Some Notes on Monetary Theories of the Trade Cycle - Shackle, G. L. S. (Review of Economic Studies, 1933)
Journal Article Some Notes on Monetary Theories of the Trade Cycle Get access G. L. S. Shackle G. L. S. Shackle Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 1, October 1933, Pages 27–38, https://doi.org/10.2307/2967435 Published: 01 October 1933